2023
DOI: 10.3390/ijerph20031669
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Outdoor versus Indoor Exercise on Psychological Health, Physical Health, and Physical Activity Behaviour: A Systematic Review of Longitudinal Trials

Abstract: A growing body of research is exploring the potential added health benefits of exercise when performed outdoors in nature versus indoors. This systematic review aimed to compare the effects of exercise in outdoor environments versus indoor environments on psychological health, physical health, and physical activity behaviour. We searched nine databases from inception to March 2021 for English language, peer-reviewed articles: MEDLINE, Embase, PubMed, Scopus, Web of Science, CINAHL, SportsDiscus, GreenFile, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Combining physical activity with direct exposure to nature may enhance mood, as both regular exercise and outdoor green environments can increase happiness and reduce stress [ 20 , 23 , 27 , 67 ]. Noseworthy et al [ 5 ] found that outdoor exercise is associated with higher levels of enjoyment, vitality, positive engagement, and intention to return to exercise than indoor exercise. Lu and Hu [ 68 ] found that extraversion is significantly correlated with almost all types of leisure engagement, whereas neuroticism is unrelated to leisure engagement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Combining physical activity with direct exposure to nature may enhance mood, as both regular exercise and outdoor green environments can increase happiness and reduce stress [ 20 , 23 , 27 , 67 ]. Noseworthy et al [ 5 ] found that outdoor exercise is associated with higher levels of enjoyment, vitality, positive engagement, and intention to return to exercise than indoor exercise. Lu and Hu [ 68 ] found that extraversion is significantly correlated with almost all types of leisure engagement, whereas neuroticism is unrelated to leisure engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activities and exercise programs during leisure time are important to promoting quality of life and overall well-being [ 1 , 2 , 3 ]. Research shows that regular leisure-time physical activity can help in the prevention or management of many chronic physical conditions [ 4 , 5 ]. It can also improve social, emotional, and mental well-being by reducing depression, stress, and social physique anxiety [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, hiking with regularity favors an improvement in general physical fitness [44,45]. In addition, hiking contributes towards the previously described benefits to cognitive abilities, and it is reasonable to assume that the individual who practices sport in a natural setting can benefit from further advantages [46]. Atchley and Strayer (2012) [47] hypothesized that the natural environment itself can have a positive impact on cognitive functions such as selective attention, problem-solving, and inhibition.…”
Section: Introductionmentioning
confidence: 99%